Soil analysis as a feasibility study of a ground sink heat pump for air conditioning system - Muhammad Wafiuddin Hasanudin (Penerbit Universiti Malaysia Perlis, 2011)
The rapid development and also the increasing of the population make the used of energy demands increase. Thus, the efficient energy utilization getting very important due to environmental energy problem such as global warming and increasing of oil price. The alternative to solve the problem is by using the clean energy and also renewable energy such as ground sink heat pump (GSHP). The soil analysis is very important in built effective GSHP. The properties of the soil that has been determined for the GSHP system were thermal conductivity and thermal diffusivity. The method used to determine the thermal conductivity and thermal diffusivity was hot wire method in the trenches depth 1.5 meter at the purposed site in School of Environmental Engineering. The hot wire method was compared with the thermal handbook properties to determine thermal properties of the soil by knowing the types of soil by using sieve analysis and percentage of the moisture content. The thermal conductivity and thermal diffusivity of sand and clay were determined to identify the thermal properties for different types of soil.